Comparison of Demographic Life‐History Traits of the Snake‐Eyed Skink: Observations From an Island and a Mainland Population - Mehtap Ağdağ; Mehmet Zülfü Yıldız; Abdullah Altunışık (Ecology and Evolution)
ABSTRACT The life‐history traits of animals are influenced by several factors. It has been proposed that key factors such as competition, predation pressure, and resource availability may differ between mainland and island populations of the same species. In this context, our study focused on an island (Yayla, Cyprus) and mainland (Hassa, Türkiye) populations of the snake‐eyed skink, Ablepharus budaki. This study aimed to reveal both intra‐population and inter‐population relationships in terms of mean age, longevity, age at maturity, body size, and sexual dimorphism. Our results show that lizards in the island population had longer lifespans and higher mean ages than the mainland population. Nevertheless, both populations were comparable in terms of mean body size. We also concluded that island individuals reach sexual maturity approximately 1 year later than their mainland conspecifics, and sexual dimorphism in terms of size is observed only in the mainland population. This study, offering initial demographic insights into the non‐mainland population of the species, provides the reason for additional research in this field.